Substantiation of thermomechanical technology parameters of absorbing levels isolation of the boreholes - Sudakov, A.; Dreus, A.; Ratov, B.; Sudakova, O.; Khomenko, O.; Dziuba, S.; Sudakova, D.; Muratova, S.; Ayazbay, M. (My University, 2020)
The aim of the work is to improve the thermomechanical absorption insulation technology horizons of drilling wells by the established regularities of change and the substantiation of its regime parameters from the composition and physical-mechanical properties strengthen thermoplastic composite material and, on this basis, development a technological regulation containing recommendations on the manufacture of composites and organizations laying work, designing and isolation of the absorption zones of the washing liquid in the drilling rigs wells. The tasks set were solved by complex method research that contains analysis and synthesis of literary and patent sources, conducting analytical, experimental and industrial research. Experimental processing data was carried out using methods of mathematical statistics. Experimental research is carried out using the provisions of the theory of scientific experiment and theory random processes. The evaluation of the effectiveness of the results was carried out in production conditions.
Keywords: drilling of boreholes; isolation; absorbing level; melting; backfill materials